Pola permukiman di dusun Mantran Weran Magelang dalam bingkai kebudayaan Jawa - Refranisa (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Dusun Mantran Wetan is a hamlet located at the foot of Mount Andong of Magelang Regency whose majority of its inhabitants are people with Javanese-Islam acculturation background. Communal rituals of Javanese tradition are still well-preserved and practiced in certain spaces that allow a forming of a settlement pattern of the hamlet. This study aims to improve and deepen people’s scientific knowledge of settlement pattern of Dusun Wetan Mantran Magelang in the frame of Javanese culture as well as to support the effort to preserve the settlement pattern of the hamlet. An empirical approach was used in this study. The data were collected through field observations, interviews, and from a number of Javanese culture literatures. This study reports that there exist two sacred places/shrines and two communal spaces as center points where people hold their communal rituals. To conclude, well-preserved Javanese cultural symbolization established in the community determines the settlement pattern of Dusun Mantran Wetan. © 2019 Refranisa